2007
DOI: 10.2174/138161207781368837
|View full text |Cite
|
Sign up to set email alerts
|

How to Advise Aspirin Use in Patients Who Need NSAIDs

Abstract: NSAIDs are widely used all over the world. NSAID use is rising due to increasing availability without a prescription, use of aspirin for prevention of thrombotic disorders and the ageing population. Aspirin is used as an analgesic drug in many countries, but the main current indication is low-dose aspirin for the prevention of cardiovascular events. However, NSAIDs and aspirin use account for approximately 20-25% of all reported drug adverse events. Most of those are gastrointestinal including dyspepsia, hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 85 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Aspirin (acetylsalicylic acid) is used as an analgesic drug in many countries and together with other NSAIDs, it accounts for approximately 20–25% of overall reported drug adverse events. Most of these are gastrointestinal (GI) events, which include dyspepsia, mucosal injury and more serious events, such as ulcers, GI bleeding and perforation 5–7 . Therefore, the inappropriate use of drugs is a matter of interest to public health authorities, drug regulatory agencies and professional prescribers as well.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Aspirin (acetylsalicylic acid) is used as an analgesic drug in many countries and together with other NSAIDs, it accounts for approximately 20–25% of overall reported drug adverse events. Most of these are gastrointestinal (GI) events, which include dyspepsia, mucosal injury and more serious events, such as ulcers, GI bleeding and perforation 5–7 . Therefore, the inappropriate use of drugs is a matter of interest to public health authorities, drug regulatory agencies and professional prescribers as well.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Poor tolerability due to upper gastrointestinal symptoms, often categorized as dyspepsia, is a significant cause of treatment discontinuation 18. The prevalence of dyspepsia in patients treated with traditional NSAIDs can be high, ranging from 5%–50% 19. Due to the role of the COX-2 isoenzyme in renal prostaglandin biosynthesis, both traditional and selective NSAIDs are associated with renovascular AEs; risk may be increased in agents with a longer half-life 20,21…”
Section: Use Of Oral Nsaids In the Management Of Soft Tissue Injuriesmentioning
confidence: 99%
“…In a recent Internet survey of 1,000 general practitioners in the United States, 85% of providers indicated that more than 25% of their patients were taking aspirin for preventive reasons 84. The concomitant use of low-dose aspirin and oral NSAIDs has been associated with an increased risk of serious gastrointestinal AEs 19. Although the use of gastroprotective agents, such as proton pump inhibitors, appears to lower the risk of serious gastrointestinal AEs, not all patients on NSAID therapy receive these agents 84.…”
Section: Diclofenac Epolamine Topical Patchmentioning
confidence: 99%
“…Many patients with ankle sprains may also be taking low dose aspirin (LDA) or other antiplatet therapies for cardioprophylaxis, placing them at increased risk for GI events when NSAIDs are used 13. In addition, some commonly used NSAIDs, such as naproxen and ibuprofen, but not diclofenac, can have pronounced effects on the antiplatelet properties of LDA 1418…”
Section: Introductionmentioning
confidence: 99%